Fast Facts: Specific Learning Difficulties - Kirby, Amanda; Kaplan, Bonnie J (S. Karger, 2003)
As more and more children present to family physicians with learning and attention problems, the overlap between the concerns of health and education professionals can become confused. Furthermore, dyslexia, developmental coordination disorder and attention deficit hyperactivity disorder often occur together, with each other and with oppositional defiant disorder, conduct disorder, Asperger's syndrome or obsessive-compulsive disorder.'Fast Facts: Specific Learning Difficulties' is a practical guide for family physicians, specialist nurses and other healthcare professionals whose role it is to help and treat patients and their carers. It reviews five learning and behavioural problems addressing four questions for each:• What is the disorder, including its core symptoms and signs, what is its incidence and prevalence, and what is known about its cause?• What are the criteria for this disorder as specified by the Diagnostic and Statistical Manual of Mental Disorders 4th Edition?• Who assesses and diagnoses this disorder, and how?• What are the treatments for this disorder, and how?• What are the treatments for this disorder, including management at home and in school?This is an applied and practical guide which will clarify and enhance the role of the primary care physician in the treatment and management of these disorders.Contents:• General issues of diagnosis and treatment• Dyslexia (reading disability)• Developmental coordination disorder (dyspraxia)• Attention deficit hyperactivity disorder• Oppositional defiant disorder and conduct disorder• Asperger’s syndrome• Obsessive-compulsive disorder• Future trends
Keywords: Learning Disabilities; poruchy učení; neurologie; psychiatrie; Psychiatry